From face-to-face to face-to-screen: remote management, effectiveness and accountability of humanitarian action in insecure environments. (3rd July 2014) - Donini, Antonio; Maxwell, Daniel
Abstract This article provides a first attempt at analysing the complex set of issues around remote management practices in insecure environments and their increased use. It looks at definitions and reviews existing published and grey literature on remote management and related practices. It tries to situate remote management in the evolving context of post-Cold War strategies of dealing with conflict and crisis. On the basis of interviews with a cross-section of aid workers, senior headquarters managerial and policy staff, donors, and research institutions, it provides an assessment of current remote management practices, with a particular focus on Afghanistan and Somalia, and their implications for the future of humanitarian action.